Assessment of Opuntia ficus-indica supplementation on enhancing antioxidant levels - Zaman, Rahela; Sin, Eugenie Sing Tan; Ahmad Bustami, Normina; Amini, Farahnaz; Seghayat, Marjan Sadat; Yu, Bin Ho; Chung, Keat Tan (Nature Research, 2025)
Opuntia ficus-indica (OFi) is a major fruit source prevalent in semiarid and arid regions across various countries worldwide. It is widely recognised for its potential health benefits; however, most studies investigating its effects have been limited to pre-clinical models, highlighting the need for further validation through clinical trials. This study aimed to evaluate the effectiveness of OFi supplementation in enhancing antioxidant levels. Fifty healthy participants, aged 18 years and older, including males and females, received a daily OFi supplement of 1500 mg for 3 months. These findings revealed a significant 48.1% increase in salivary total antioxidant capacity (TAC) (P < 0.001), indicating improved antioxidant activity. Simultaneously, oxidative stress biomarkers showed substantial reductions: malondialdehyde (MDA) decreased by 28.3%, nitrotyrosine (3-NT) decreased by 51.5%, and 8-hydroxy-2’-deoxyguanosine (8-OHdG) decreased by 59.8% (P < 0.001). Furthermore, participants reported a 20.1% improvement (P < 0.001) in Visual Analogue Scales (VAS), reflecting a notable enhancement in overall well-being. In conclusion, OFi exhibited promising efficacy in elevating antioxidant levels and mitigating oxidative stress. These findings suggest its potential as an adjuvant therapy for managing chronic conditions associated with oxidative stress.